La certificación del banano orgánico y su incidencia en la rentabilidad de la Asociación de Pequeños Agricultores y Ganaderos del Algarrobal - Chepén año 2018 - Medina Sánchez, Carlos Omar (2018)
This research is related to the study of the certification of organic bananas in relation to its impact on the profitability of the Association of Small Farmers and Livestock Farmers of the Algarrobal in the province of Chepén, the main objective is to determine the incidence of the certification of the organic banana in improving the profitability of the association mentioned before; has been considered the population, two associations that operate to date, located in the valleys of Chira - Sullana - Piura, Batan Grande - Lambayeque and Jequetepeque - Chepén - La Libertad, taking as sample, eighteen certified partners with presence in the valley of Batan Grande - Lambayeque and thirty-seven certified members of the valley of Jequetepeque - La Libertad of the Association of Small Farmers and Cattlemen of the Algarrobal, for this, the descriptive - comparative method will be applied, which will allowed to know the current situation of the association and compare the information in the different scenarios found in the present study. The most important results have been to describe the economic and financial situation, through of financial indicators; likewise, the impact on profitability has been compared with certification and without certification; in the same way, the investment in the certification of organic bananas has been analyzed. The most significant conclusion is have determined that the certification of organic bananas has impacted favorably the improvement of the profitability of the Association of Small Farmers and Cattle Ranchers of the Algarrobal in 2017, which is reflected in the growth of the result of the exercise or net profit.